2020
DOI: 10.2147/ijwh.s267691
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluation of the Cesarean Scar Niche In Women With Secondary Infertility Undergoing ICSI Using 2D Sonohysterography Versus 3D Sonohysterography and Setting a Standard Criteria; Alalfy Simple Rules for Scar Assessment by Ultrasound To Prevent Health Problems for Women</p>

Abstract: Background Many expressions were used to define the defect that is seen by ultrasound after cesarean section (CS) namely scar defect, niche, isthmocele, uterine pouch or diverticula. Objective To compare the accuracy of 2 dimensional sonohysterography (2D SHG) to 3 dimensional sonohysterography (3D SHG) in evaluating cesarean section uterine scar depth (D), base width (BW), width (W) and residual myometrial thickness (RMT) in women with secondary infertility and establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The study by M. Alalfy showed that 3D sonohysterography is as accurate in assessing the uterine niche after cesarean section as 2D sonohysterography. However, the use of 3D sonography provide better characterization of the cesarean scar niche, because of superior evaluation of the RMT and niche width before the Intracytoplasmic Sperm Injection [20].…”
Section: Three-dimensional (3d) Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by M. Alalfy showed that 3D sonohysterography is as accurate in assessing the uterine niche after cesarean section as 2D sonohysterography. However, the use of 3D sonography provide better characterization of the cesarean scar niche, because of superior evaluation of the RMT and niche width before the Intracytoplasmic Sperm Injection [20].…”
Section: Three-dimensional (3d) Imagingmentioning
confidence: 99%
“…According to some authors, the best time to perform an ultrasound examination is when the endometrial thickness is the smallest, it means immediately after the menstruation [33]. In another publication, the best time is during/after a few days after the menstruation [20]. According to the modified Delphi protocol, the ultrasound niche evaluation between 7.-14. cycle day may prevent the need for additional infusion fluid due to its natural intrauterine occurrence in the midfollicular phase [3].…”
Section: In Which Phase Of Menstrual Cycle Should We Assess Uterine Niche?mentioning
confidence: 99%
“…It is proved that the US scan is the most valuable, repeatable, and cost-effective technique [18,19]. Scar niche can be assessed by a combined integrated 2D and 3D US scan with new specific geometrical and anatomical considerations [20].…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional sonohysterography gives the examiner a more detailed image of the niche with regard to base width and scar depth. More precise data leads to a better prediction of the outcome in future pregnancies and is important to guide follow-up niche management [24,25].…”
Section: Post-cesarean Nichementioning
confidence: 99%